2021
DOI: 10.3389/fonc.2020.531244
|View full text |Cite
|
Sign up to set email alerts
|

MiR-1539 and Its Potential Role as a Novel Biomarker for Colorectal Cancer

Abstract: PurposeWe investigated microRNA (miR) 1539 as a potential biomarker for predicting the risk and pathobiological behavior of colorectal cancer (CRC).MethodsOur strategy consisted of analyzing 100 serum samples from 51 CRC patients, 49 healthy controls (HCs), and another 56 CRC tissue and matched normal adjacent to tumor (NAT) samples. The relative expression levels of miR-1539 in exosomes, serum and tissues were detected and compared in the different groups, using reverse transcription-polymerase chain reaction… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 52 publications
0
4
0
Order By: Relevance
“…Microarray analyses of serum exosomal‐derived miRNAs in 88 colorectal cancer patients revealed differential expression of seven miRNAs including miR‐1229, let‐7a, miR‐150, miR‐223, miR‐1246, miR‐21, and miR‐23a compared with healthy control (Ogata‐Kawata et al, 2014). Intriguingly, Cui, showed increased MiR‐1539 expression in exosomes from colorectal cancer patients and its correlation with poorer pathologic differentiation of tumor, highlighting its possible use as a biomarker for screening and a predictor of poor clinicopathological behavior in colorectal cancer (Cui et al, 2020).…”
Section: Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Microarray analyses of serum exosomal‐derived miRNAs in 88 colorectal cancer patients revealed differential expression of seven miRNAs including miR‐1229, let‐7a, miR‐150, miR‐223, miR‐1246, miR‐21, and miR‐23a compared with healthy control (Ogata‐Kawata et al, 2014). Intriguingly, Cui, showed increased MiR‐1539 expression in exosomes from colorectal cancer patients and its correlation with poorer pathologic differentiation of tumor, highlighting its possible use as a biomarker for screening and a predictor of poor clinicopathological behavior in colorectal cancer (Cui et al, 2020).…”
Section: Applicationsmentioning
confidence: 99%
“…However, more recent studies demonstrated favorable role of exosomal microRNA for diagnosing pancreatic cancer, whereas high levels of exosomal miR-181a, miR-10b, miR-30c, miR-21, and low levels of exosomal miR-let7a can differentiate pancreatic cancer from normal control and chronic pancreatitis patients (Lai et al, 2017). On the contrary, Q. Wei et al patients and its correlation with poorer pathologic differentiation of tumor, highlighting its possible use as a biomarker for screening and a predictor of poor clinicopathological behavior in colorectal cancer (Cui et al, 2020).…”
Section: Exosomes As Diagnostic Markers In Cancermentioning
confidence: 99%
“…Milk-derived extracellular vesicles can play an important role in intercellular information transfer as highquality nanocarriers (Babaker et al, 2022), encapsulation of anthocyanins in Milk-derived extracellular vesicles enhances the anti-proliferative and anti-inflammatory effects on various cancer cells without toxic side effects, achieving better efficacy (Munagala et al, 2017). Cui et al (2020) found that miR-1539 was overexpressed in CRC tissues and serum of CRC patients, suggesting changes in tumor location and poor prognosis, and could be used as a novel potential biomarker for CRC screening.…”
Section: The Role Of Infected Bacterial Sevs In Crc Progressionmentioning
confidence: 99%
“…Furthermore, plasma collected from CRC patients was found to express important levels of exosomal miRNA-27a and miRNA-130a [ 140 ]. A different study found upregulation of miRNA-1359 in exosomes isolated from CRC patients, leading to an accurate differentiation of CRC cases from healthy individuals [ 141 ]. Exosomal miRNAs are receiving a growing interest, with several other studies aiming to identify and validate promising biomarkers for early CRC diagnosis and population screening [ 131 , 142 , 143 , 144 ].…”
Section: Liquid Biopsymentioning
confidence: 99%